Developments in work-related upper limb disorders (WRULD) amongst Dutch university students from 2004 to 2014. - Dekker, Marijke C.; van Egmond, René; Molenbroek, Johan F.M.; Vink, Peter (Work, 2021)
BACKGROUND: Former studies on work-related upper limb disorders (WRULD) within university education report substantial prevalence rates. In this study, developments in WRULD amongst students in the period 2004–2014 were investigated. Our findings can be a benchmark for future studies, in particular when there are major societal changes as in the case of the COVID-19 pandemic. OBJECTIVE: Differences in time (academic year), how long students have been studying (year of studying), relations with computer time and societal changes were points of interest. METHODS: 2254 students (average age 20.0 years) responded to a questionnaire on WRULD. Students experiencing complaints were further questioned about the severity of complaints and associated body locations. RESULTS: The average percentage of students experiencing complaints was 57%. The highest prevalence rates and severity scores were found in the first and last recorded academic years. The neck, shoulder, back and wrist were most often indicated. The prevalence of complaints raised from the 1st (49%) to the 4th (75%) year of studying. Two seriousness measures showed highest scores in the 5th/6th/7th year of studying. Relations were found between both the prevalence and seriousness of complaints with reported computer time. CONCLUSIONS: After an initial decreasing trend from the academic year 2006/2007 to 2010/2011 there was an increase in WRULD amongst students from 2010/2011 to 2013/2014. Limiting financial and study time factors may have played a role. Structural attention for WRULD prevention and risk factors seems to be effective in reducing prevalence and severity of WRULD. This seems to be even more necessary due to recent COVID-related changes in the students' lives.